Development of gas chromatography-mass spectrometry detection procedure to determine fatty acids in special formula milk powder - Ning Wang; Xiaoqing Shao; Mengyao Huang; Cunfang Wang; Hua Jiang; Xiaoning Zhang (Food Science of Animal Products)
In the future, the supply and variety of foods for special medical purposes (FSMPs) available on the market are expected to keep increasing. However, no fatty acid detection method specifically for FSMPs, especially special formula milk powder, has yet been established in China. This paper reports a rapid and accurate method based on gas chromatography-mass spectrometry (GC-MS) for the determination of fatty acids in special formula milk powder. The results showed that ultrasound-assisted lipid extraction in the solution state, methyl esterification of the fatty acids with the solution of sodium methoxide in methanol, a defined GC-MS temperature program, and a split ratio of 10:1 gave the best results. The linearity (correlation coefficients: 0.995 9–0.999 7), precision (relative standard deviation (RSD): 0.41%–3.36%), stability (RSD: 1.01%–4.91%), repeatability (RSD: 1.02%–3.81%), and spiked recovery rate (90.03%–107.76%) of the proposed method were confirmed to meet the detection requirements. Finally, the method performance was evaluated for nine commercial products, and the results revealed that the method was cheaper than that used in the national standard for the determination of fatty acids in food (GB 5009.168–2016) and the analysis time was shortened by 0.5 h. Compared to the international standard for the determination of fatty acids (AOAC 996.06), this method subdivides fatty acids and is more comprehensive in terms of detection accuracy and applicability. In conclusion, the proposed method enables the efficient and accurate detection of fatty acids in FSMPs.